PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN ASING TERHADAP PENGUNGKAPAN ESG (Studi Empiris Pada Perusahaan Yang Terdaftar di BEI Tahun 2020 – 2022) - TAMBUNAN, RONIA; WAHYULIZA, SUCI (JURNAL AKUNTANSI DAN KEUANGAN, 2024)
The purpose of this study is to ascertain how management, institutional, and foreign ownership affect ESG disclosure in businesses that are listed on the Indonesia Stock Exchange. Secondary data from the annual reports of businesses listed on the Indonesia Stock Exchange is used in research. 22 businesses that were listed between 2019 and 2022 on the Indonesia Stock Exchange served as the sample for this study. The data collection method involved gathering as much information as possible and utilizing SPSS 26 to analyze it. The study's findings indicate that foreign and institutional ownership have an impact on ESG disclosure. The impact of managerial ownership on ESG disclosure is zero.